Application of Drone Technology in Agriculture and Technologies & Strategies for Beekeepers to Adapt to Climate Change - Funja, Rose (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
Guest speakers: Ms. Rose Funja, Maniging Director, Agrinfo - Tanzania, Mr. Miguel Huertas, Ministry of Agriculture, Coordinator, Food Security and Enterprise - Belize